2020
DOI: 10.3920/bm2019.0142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotics on the maintenance of intestinal homeostasis after chemotherapy: systematic review and meta-analysis of pre-clinical studies

Abstract: Gastrointestinal mucositis (GIM) is an inflammation caused by antitumor therapy, especially after chemotherapy and radiotherapy. Currently in the clinical practice, only palliative measures are taken to treat GIM, representing the main clinical limitation in the management of this condition. Several studies have highlighted the potential benefits of probiotics for the management of GIM, but the actual role of these microorganisms in the maintenance of intestinal homeostasis remains elusive. In this context, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…According to Tourkochristou et al, upon the activation of P r e p r i n t NLRP3, apoptosis-associated speck-like protein (ASC) could trigger the activation of caspase-1, which helps to produce mature IL-1β and IL-18 and induce chronic intestinal inflammation (21)(22)(23). Also, it was found that the continuous between the harmful gut bacteria and the pathogenassociated molecular patterns will accelerate the activation of NLRP3 inflammasome, which results in severer inflammatory reactions by the subsequent upregulation of the downstream pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), interleukin-1β (IL-1β) and interleukin-18 (IL-18), thereby further aggravating the inflammatory reaction (24,25). Accordingly, compared with the MOX (-) patient group, we found that moxibustion in the MOX (+) patient group not only suppressed the expression of NLRP3, but also inhibited expression of pro-inflammatory factors such as TNF-α, IL-1β, IL-6 and IL-18 while promoting the level of IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…According to Tourkochristou et al, upon the activation of P r e p r i n t NLRP3, apoptosis-associated speck-like protein (ASC) could trigger the activation of caspase-1, which helps to produce mature IL-1β and IL-18 and induce chronic intestinal inflammation (21)(22)(23). Also, it was found that the continuous between the harmful gut bacteria and the pathogenassociated molecular patterns will accelerate the activation of NLRP3 inflammasome, which results in severer inflammatory reactions by the subsequent upregulation of the downstream pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), interleukin-1β (IL-1β) and interleukin-18 (IL-18), thereby further aggravating the inflammatory reaction (24,25). Accordingly, compared with the MOX (-) patient group, we found that moxibustion in the MOX (+) patient group not only suppressed the expression of NLRP3, but also inhibited expression of pro-inflammatory factors such as TNF-α, IL-1β, IL-6 and IL-18 while promoting the level of IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…After a full analytical reading, all data of interest were summarized in Table 1 for further analysis and interpretation. Furthermore, the data regarding mortality rate and viral load in the lung of mice with virus‐induced lower respiratory tract infection treated or not with quercetin and its derivatives were pooled to estimate the mean difference and the confidence intervals by meta‐analysis using Review Manager (RevMan)® 5.3 software (Lima et al, 2020b). All pooled data were estimated using a random effect model (Lima, Silva Alves, Sanches, Antunes Fernandes, & de Paiva, 2019; Lima, Souza, Fernandes, Cardoso, & Godói, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the combination has little effect on probiotic bacteria ( Lactobacillus plantarum , Lactobacillus Paracasei , Bifidus animalis ), whereas gentamycin kills all of them [ 29 ]. This effect is relevant because many of the adverse drug reactions are related to their activity on the gut microbiota, which can lead to diarrhea, nausea, vomiting and even chronic changes in the gut mucosa [ 103 ].…”
Section: Toxicitymentioning
confidence: 99%